Composite flame-retardant material with high relative leakage index and high glowing filament as well as preparation method and application of composite flame-retardant material
By using flame retardant with specific proportion and particle size distribution in flame retardant materials to form a flame retardant network, the problem of the relatively low leakage index of existing flame retardant materials under high temperature and high voltage conditions is solved, and the high glow wire temperature and safety performance is improved, while meeting environmental protection and regulatory requirements.
Patent Information
- Application Number
- CN202510094821.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing flame retardant materials have a relatively low leakage index under high temperature and high voltage conditions, making it difficult to meet the requirements of electronic and electrical products for high glow wire temperature and safety performance. At the same time, there are environmental protection and regulatory compliance issues.
Aluminum alkyl hypophosphate, polyaluminum phosphate and metal hydroxide are used as flame retardants. By adjusting their particle size parameters and proportions, a flame retardant network with a certain particle size distribution is formed to improve the flame retardant performance and relative leakage index of the composite material.
It significantly improves the glow wire performance and relative leakage index of polyamide flame retardant composite materials, ensuring safe storage and use under high temperature or high voltage conditions, while meeting environmental protection and regulatory requirements.
Smart Images

Figure BDA0005252555930000021 
Figure BDA0005252555930000051 
Figure BDA0005252555930000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, in particular to a high relative leakage index, high glow-wire composite flame retardant material and a preparation method and application thereof. Background Art
[0002] PA66, also known as polyamide 66 or nylon 66, modified flame-retardant PA66 products are widely used in automobiles, electronic appliances and power tools. At present, the common flame retardant scheme for PA66 on the market is to use brominated flame retardants such as decabromodiphenylethane and brominated polystyrene. Brominated flame retardants have good temperature resistance and high flame retardant efficiency, but they are not very environmentally friendly. At the same time, RoHS regulations limit the content of polybrominated biphenyls and polybrominated diphenyl ethers to less than 1000ppm, resulting in many products that cannot use brominated flame retardants. The common flame retardants in halogen-free flame retardant systems are mostly organophosphorus flame retardants. The more common system is a compound of ADP (aluminum diethylphosphinate) and MCA (melamine cyanurate). The GWIT of this system can reach 750°C. However, due to the latest REACH regulations adding melamine as a key concern substance, many manufacturers have begun to refuse to use flame-retardant nylon materials with excessive melamine content. Using ADP alone, its GWIT cannot reach 750℃. Now the requirements for electronic and electrical products are getting higher and higher. Some products even require GWIT ≥ 800℃, and require a high relative leakage index to ensure safety. Among the current flame-retardant materials, the relative leakage index is relatively low and still needs to be further improved.
[0003] Therefore, it is necessary to provide a flame retardant material with high relative leakage index, high glow wire, halogen-free, and melamine-free. Summary of the invention
[0004] The object of the present invention is to provide a high relative leakage index and high glow-wire flame-retardant composite material in order to overcome the above-mentioned defects in the prior art.
[0005] Another object of the present invention is to provide a method for preparing the high relative leakage index and high glow-wire flame-retardant composite material.
[0006] Another object of the present invention is to provide an application of the high relative leakage index and high glow-wire flame-retardant composite material in the preparation of electronic products and flame-retardant products.
[0007] To achieve the above object, the first aspect of the present invention provides a high relative leakage index and high glow-wire flame-retardant composite material, which comprises the following components in parts by weight:
[0008]
[0009] The flame retardant includes alkyl aluminum hypophosphite, polyaluminum phosphite and metal hydroxide, and the particle size parameter K is defined as D V10 +3D V50 +D V90 , satisfying: K A >K B >K C ;
[0010] K A , K B , K C They correspond to the particle size parameters K of alkyl aluminum hypophosphite, polyaluminum phosphite and metal hydroxide respectively;
[0011] D V10 It indicates the particle size corresponding to when the volume of the flame retardant reaches 10%, in μm;
[0012] D V50 It indicates the particle size corresponding to when the cumulative volume of the flame retardant reaches 50%, in μm;
[0013] D V90 It indicates the particle size when the cumulative volume of the flame retardant reaches 90%, in μm.
[0014] The present invention further designs and matches the types and particle size parameters of the flame retardant, thereby improving the dispersion performance of the flame retardant in the polyamide matrix, forming a flame retardant network with a certain particle size distribution in the polyamide matrix, and improving the flame retardant performance of the composite material; at the same time, the flame retardant network with a specific structure is also conducive to the dispersion of other components in the matrix, especially polysiloxane, which can improve the interaction with the polyamide matrix. Under the joint action of the three, the relative leakage index of the polyamide flame retardant composite material is further significantly improved, and the storage and use safety performance under humid or high voltage conditions is improved.
[0015] The polyamide resins commonly used in the art can be used in the present invention, and the polyamide includes but is not limited to polyamide 6 (PA6) and polyamide 66 (PA66).
[0016] Preferably, the weight ratio of alkyl aluminum hypophosphite, polyaluminum phosphite and metal hydroxide in the flame retardant is: alkyl aluminum hypophosphite: polyaluminum phosphite: metal hydroxide = (5-16): (6-12): 1. The three flame retardants work together to improve the glow wire performance of the composite flame retardant material.
[0017] Preferably, the alkyl aluminum hypophosphite is diethyl aluminum hypophosphite (ADP).
[0018] Preferably, the polyaluminium phosphite contains crystal water, and the content of crystal water is 1-3 wt %. An appropriate content of crystal water helps to enhance the synergistic effect between the three flame retardants, but the content of crystal water cannot be too high, which may easily lead to difficulties in extrusion processing.
[0019] Common metal hydroxide flame retardants in the art can be used in the present invention, and the metal hydroxide includes but is not limited to at least one of aluminum hydroxide and magnesium hydroxide.
[0020] Preferably, the particle size of the alkyl aluminum hypophosphite satisfies: 100 μm<K A ≤125μm;
[0021] Preferably, the particle size of the polyaluminium phosphite satisfies: 75 μm<K B ≤100μm;
[0022] Preferably, the particle size of the metal hydroxide satisfies: 10 μm ≤ K C ≤20μm.
[0023] In the present invention, when the particle size distribution of each flame retardant in the flame retardant meets a specific range, the glow wire performance and electrical insulation performance of the composite flame retardant material can be further improved. The particle size distribution parameter is defined as η = (D V90 -D V10 ) / D V50 .
[0024] Preferably, the particle size distribution of the alkyl aluminum hypophosphite is denoted as η A , 1.6≤η A ≤2.0.
[0025] Preferably, the particle size distribution of the polyaluminium phosphite is denoted as η B , 1.5≤η B ≤1.8.
[0026] Preferably, the particle size distribution of the metal hydroxide is denoted by η C , 1.3≤η C ≤1.5.
[0027] Preferably, the particle size of the alkyl aluminum hypophosphite satisfies: D V10 6.7-8.1μm; D V50 19-21.5μm; D V90 38.1-50.2μm.
[0028] Preferably, the particle size of the polyaluminium phosphite satisfies: D V10 1.82-4.5μm; D V50 16.1-18.2μm; D V9025.8-36.3μm.
[0029] Preferably, the particle size of the metal hydroxide satisfies: V10 0.68-1.1μm; D V50 2.9-3.6μm; D V90 4.8-6.4μm.
[0030] Optionally, the coupling agent includes but is not limited to at least one of 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0031] Optionally, the lubricant includes but is not limited to at least one of pentaerythritol stearate and N,N'-ethylene bisstearamide.
[0032] Optionally, the antioxidant includes but is not limited to at least one of N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, tris(2,4-di-tert-butylphenyl)phosphite, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0033] The second aspect of the present invention provides a method for preparing the high relative leakage index and high glow-wire flame-retardant composite material according to the first aspect of the present invention, comprising the following steps:
[0034] According to the weight parts, add the flame retardant and coupling agent into the low mixer, mix for 5-8 minutes, and stir evenly, which is recorded as material 1;
[0035] Add the remaining raw materials into the high-speed mixer, and then pour 40-60% of the weight of material 1 into the high-speed mixer, mix for 60-90 seconds, and stir evenly, which is recorded as material 2;
[0036] Material 2 is discharged from the main feeding hopper, and the remaining material 1 is discharged from the side feeding hopper, and the high relative leakage index and high glow-wire flame-retardant composite material is prepared after being processed by co-rotating twin-screw extrusion, cooling and pelletizing.
[0037] Preferably, the rotation speed of the low mixer is 50-150 rpm / min.
[0038] Preferably, the rotation speed of the high speed mixer is 1500-3000 rpm / min.
[0039] Preferably, the rotation speed of the twin-screw extruder is 200-350 rpm / min.
[0040] Preferably, the twin-screw extrusion temperature is 220-285°C.
[0041] Preferably, the screw length-to-diameter ratio of the twin-screw extruder is (40-44):1.
[0042] In the twin-screw extruder, the screw diameter is 35-65 mm. In addition, the single screw assembly has a total of 6 groups (two in each group) of shear thread elements, 4-5 groups of 45° shear thread elements, 1-2 groups of 60° shear thread elements, and no 90° strong shear thread elements.
[0043] The third aspect of the present invention provides the use of the high relative leakage index and high glow-wire flame-retardant composite material according to the first aspect of the present invention in the preparation of electronic products and flame-retardant products.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The composite flame retardant material of the present invention has both high glow wire performance and relative leakage index. Among them, the glow wire temperature is above 750°C under the condition of 2.0mm, and the glow wire temperature is above 780°C under the condition of 3.0mm; the relative leakage index is above 500V and can be as high as 600V. It is more environmentally friendly and safe, and the glow wire GWIT is greatly improved, which broadens the application scenarios of flame retardant materials. DETAILED DESCRIPTION
[0046] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.
[0047] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention are as follows:
[0048] Polyamide: nylon 66, EPR24, purchased from Henan Shenma;
[0049] Flame retardant:
[0050] Aluminum diethylphosphite (ADP): commercially available;
[0051] Polyaluminium phosphite: Al2(HPO3)3·4H2O, commercially available;
[0052] Aluminum hydroxide: commercially available;
[0053] Polysiloxane: PMX-200 2000, kinematic viscosity 2000 cSt, purchased from Dow;
[0054] Coupling agent: 3-aminopropyltriethoxysilane, KH550, commercially available;
[0055] Lubricant: N,N'-ethylene bisstearamide, commercially available;
[0056] Antioxidants:
[0057] Antioxidant 1098: N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, commercially available;
[0058] Antioxidant 168: tris(2,4-di-tert-butylphenyl)phosphite, commercially available.
[0059] Examples 1-6
[0060] This embodiment provides a series of high relative leakage index and high glow wire flame retardant composite materials, which are prepared according to the raw material formula in Table 1 and the preparation method comprising the following steps:
[0061] S1: First weigh the polyaluminium phosphite (recorded as m0) and place it in a blast drying oven, dry it at 200-230°C, and weigh it every 0.5h (recorded as m t ), according to the formula (m0-m t ) / m0*100% calculates the content of crystal water in polyaluminum phosphite, and controls the content of crystal water in the range of 1-3wt%;
[0062] S2: weigh the compound flame retardant and coupling agent according to the proportion, pour them into a low mixer, mix them evenly at a speed of 100 rpm / min (stir for about 5-8 minutes), and record them as material 1;
[0063] S3: Pour the remaining raw materials into a high-speed mixer after weighing them in proportion, and then pour 50% of material 1 into the high-speed mixer, and mix them quickly and evenly at a speed of 2500 rpm / min (stirring for about 60-90 seconds), which is recorded as material 2;
[0064] S4: discharge material 2 from the main feeding hopper, and discharge the remaining material 1 from the side feeding hopper, and process through co-rotating twin-screw extrusion (in the twin-screw extruder, the temperatures of each zone from the die head to the discharge port are set to 240°C, 260°C, 270°C, 280°C, 280°C, 280°C, 280°C, 280°C, 285°C in sequence), cooled in a water tank, and pelletized to obtain the high relative leakage index and high glow-wire flame-retardant composite material.
[0065] In the twin-screw extruder used in the present invention, the screw diameter is 35-65mm. In addition, the single screw combination has a total of 6 groups (two in each group) of shear thread elements, 4-5 groups of 45° shear thread elements, 1-2 groups of 60° shear thread elements, and no 90° strong shear thread elements.
[0066] Table 1 Raw material composition of flame retardant composite material (parts by weight)
[0067]
[0068]
[0069] Note: In Table 1, (1) the compound flame retardant is mixed according to the weight ratio of "diethyl aluminum hypophosphite: polyaluminum phosphite: aluminum hydroxide = 10:8:1"; (2) the content of crystal water in polyaluminum phosphite is 2wt%; (3) unless otherwise specified, the formula of each embodiment in Table 1 differs only in the amount of raw materials used.
[0070] Examples 7-11, Comparative Examples 1-3
[0071] A series of flame retardant composite materials are provided, which are prepared according to the method of Example 2. The difference from Example 2 is that the particle size parameters of the flame retardant are different (it should be noted that in the present invention, the purchased flame retardant raw material is ground to control its particle size distribution parameters), as shown in Table 2:
[0072] Table 2 Particle size parameters of flame retardants (in μm)
[0073]
[0074] Note: In Table 2, K = D V10 +3D V50 +D V90 ; η=(D V90 -D V10 ) / D V50 .
[0075] Example 12
[0076] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the weight ratio of diethyl aluminum hypophosphite: polyaluminum phosphite: aluminum hydroxide is 8:8:1.
[0077] Example 13
[0078] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the weight ratio of diethyl aluminum hypophosphite: polyaluminum phosphite: aluminum hydroxide is 7:6:1.
[0079] Embodiment 14
[0080] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the weight ratio of diethyl aluminum hypophosphite: polyaluminum phosphite: aluminum hydroxide is 8:5:1.
[0081] Embodiment 15
[0082] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the crystal water content of polyaluminum phosphite is 1wt%.
[0083] Example 16
[0084] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the crystal water content of polyaluminum phosphite is 3wt%.
[0085] Embodiment 17
[0086] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the crystal water content of polyaluminum phosphite is 4wt%.
[0087] Embodiment 18
[0088] This embodiment provides a high relative leakage index and high glow-wire flame-retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that in the compound flame retardant, the crystal water content of polyaluminum phosphite is 0.5wt%.
[0089] Comparative Example 4
[0090] This comparative example provides a flame retardant composite material, which is prepared by referring to the method of Example 2. The difference from Example 2 is that the flame retardant is 25 parts by weight of diethyl aluminum hypophosphite.
[0091] Comparative Example 5
[0092] This comparative example provides a flame retardant composite material, which is prepared by referring to the method of Example 2, and is different from Example 2 in that the compound flame retardant is replaced by 25 parts by weight of polyaluminum phosphite.
[0093] Comparative Example 6
[0094] This comparative example provides a flame retardant composite material, which is prepared by referring to the method of Example 2, and is different from Example 2 in that the compound flame retardant is replaced by 25 parts by weight of aluminum hydroxide.
[0095] Comparative Example 7
[0096] This comparative example provides a flame retardant composite material, which is prepared by referring to the method of Example 2, but is different from Example 2 in that polysiloxane is not added.
[0097] Performance Testing
[0098] The properties of the flame retardant composite materials obtained in the above examples and comparative examples were characterized, and the specific test items, test methods and results are as follows:
[0099] (1) UL vertical combustion: According to the UL94-2023 standard, the vertical combustion performance of the material at 1.6 mm is tested, and the flame retardant performance is divided into the following grades from best to worst: V0, V1, and V2; the flame retardant performance is worse than the V2 grade, which is indicated as "not meeting the V grade" in the present invention;
[0100] (2) Glow-wire GWIT: According to GB / T 5169.10-2017, the glow-wire ignition temperature (GWIT) of the test material at 2.0 mm and 3.0 mm, in °C;
[0101] (3) Comparative leakage index (CTI): According to IEC 60112-2020, the CTI value of the test sample with a size of 20 mm × 20 mm × 3 mm is expressed in V.
[0102] (4) Determine whether the material contains substances of very high concern (SVHCs) under the EU REACH Regulation by testing with GC-MS. If it contains, it is judged as yes; if it does not contain, it is judged as no.
[0103] The test results are shown in Table 3.
[0104] Table 3
[0105]
[0106]
[0107] From the above results we can see that:
[0108] The composite flame retardant material of the present invention has both high glow wire performance and relative leakage index. Among them, the glow wire temperature is above 750℃ under 2.0mm conditions and 780℃ under 3.0mm conditions; the relative leakage index is above 500V and can be as high as 600V. It is more environmentally friendly and safe, and the glow wire GWIT is greatly improved, which broadens the application scenarios of flame retardant materials.
[0109] The results of Example 2, Examples 7-11, and Comparative Examples 1-7 show that in the composite material, the dispersion performance of the flame retardant in the polyamide matrix can be improved by further designing and matching the type and particle size parameters of the flame retardant. The flame retardant network with a specific structure is also beneficial to the dispersion of other components in the matrix, especially polysiloxane, which can improve the interaction with the polyamide matrix. Under the joint action of the three, the glow-wire performance and relative leakage index of the polyamide flame-retardant composite material are further significantly improved, and the storage and use safety performance under high temperature or high voltage conditions is improved.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high relative leakage index, high glow-wire flame-retardant composite material, characterized in that: According to parts by weight, it includes the following components: Wherein, the flame retardant includes alkyl aluminum hypophosphite, polyaluminum phosphite and metal hydroxide, and the particle size parameter K=D is defined. V10 +3D V50 +D V90 , satisfying: K A >K B >K C ; K A , K B , K C They correspond to the particle size parameters K of alkyl aluminum hypophosphite, polyaluminum phosphite and metal hydroxide respectively; D V10 It indicates the particle size corresponding to when the volume of the flame retardant reaches 10%, in μm; D V50 It indicates the particle size corresponding to when the cumulative volume of the flame retardant reaches 50%, in μm; D V90 It indicates the particle size corresponding to when the cumulative volume of the flame retardant reaches 90%, in μm.
2. The high relative leakage index and high glow-wire flame-retardant composite material according to claim 1, characterized in that: The polyamide includes at least one of polyamide 6 and polyamide 66.
3. The high relative leakage index and high glow-wire flame-retardant composite material according to claim 1, characterized in that: The weight ratio of alkyl aluminum hypophosphite, polyaluminum phosphite and metal hydroxide in the flame retardant is: alkyl aluminum hypophosphite: polyaluminum phosphite: metal hydroxide = (5-16): (6-12):
1.
4. The high relative leakage index and high glow-wire flame-retardant composite material according to claim 1, characterized in that: Satisfy at least one of the following conditions: (1) The particle size of the alkyl aluminum hypophosphite satisfies: 100 μm<K A ≤125μm; (2) The particle size of the polyaluminium phosphite satisfies: 75 μm<K B ≤100μm; (3) The particle size of the metal hydroxide satisfies: 10 μm ≤ K C ≤20μm.
5. The high relative leakage index and high glow-wire flame-retardant composite material according to any one of claims 1 or 4, characterized in that: The particle size distribution of the flame retardant is η=(D V90 -D V10 ) / D V50 ,satisfy: (1) The particle size distribution of the alkyl aluminum hypophosphite is denoted as η A , 1.6≤η A ≤2.0; (2) The particle size distribution of the polyaluminium phosphite is denoted as η B , 1.5≤η B ≤1.8; (3) The particle size distribution of the metal hydroxide is denoted as η C , 1.3≤η C ≤1.
5.
6. The high relative leakage index and high glow-wire flame-retardant composite material according to claim 1, characterized in that: The polyaluminium phosphite contains crystal water, and the content of the crystal water is 1-3 wt %.
7. The high relative leakage index and high glow-wire flame-retardant composite material according to claim 1, characterized in that: Satisfies at least one of the following characteristics: (1) The coupling agent includes at least one of 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; (2) The lubricant includes at least one of pentaerythritol stearate and N,N'-ethylene bisstearamide; (3) The antioxidant includes at least one of N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, tris(2,4-di-tert-butylphenyl)phosphite, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
8. The method for preparing the high relative leakage index and high glow-wire flame-retardant composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: According to the weight parts, add the flame retardant and coupling agent into the low mixer, mix for 5-8 minutes, and stir evenly, which is recorded as material 1; Add the remaining raw materials into the high-speed mixer, and then pour 40-60% of the weight of material 1 into the high-speed mixer, mix for 60-90 seconds, and stir evenly, which is recorded as material 2; Material 2 is discharged from the main feeding hopper, and the remaining material 1 is discharged from the side feeding hopper, and the high relative leakage index and high glow-wire flame-retardant composite material is prepared after being processed by co-rotating twin-screw extrusion, cooling and pelletizing.
9. The method for preparing a high relative leakage index and high glow-wire flame-retardant composite material according to claim 1, characterized in that: Satisfies at least one of the following characteristics: (1) The rotation speed of the low mixer is 50-150 rpm / min; (2) The rotation speed of the high speed mixer is 1500-3000 rpm / min; (3) The speed of the twin-screw extruder is 200-350 rpm / min; (4) The temperature of the twin-screw extruder is 220-285°C.
10. Use of the high relative leakage index and high glow-wire flame-retardant composite material according to any one of claims 1 to 7 in the preparation of electronic products and flame-retardant products.
Citation Information
Patent Citations
Halogen-free and flame-retardant nylon composite with high heat conductivity and high glowing wire and preparation method of composite
CN107057350A
Halogen-free flame-retardant glass fiber reinforced nylon as well as preparation method and application thereof
CN114479446A
High-temperature-resistant flame-retardant glass fiber reinforced polyamide composite material
CN118620381A